Dampak Program GENIUS terhadap Pengetahuan Gizi Siswa: Bukti dari Kota Binjai tahun 2023: Impact of the GENIUS Program on Students’ Nutrition Knowledge: Evidence from Binjai City, 2023 - Haryana, Nila Reswari; Matanari, Grace Ballanceya Margaretha; Emilia, Esi; Purba, Edy Marjuang (Universitas Airlangga, 2026)
Background: Children’s nutrition knowledge is closely associated with dietary consumption patterns and susceptibility to infections, both of which influence nutritional status. Structured educational interventions, such as the Gerakan Edukasi dan Pemberian Pangan Bergizi untuk Siswa (GENIUS) program, represents one strategy to improve nutrition knowledge among school-aged children. Objectives: This study aimed to evaluate changes in elementary school students’ nutrition knowledge after participating in the nutrition education component of the GENIUS Program. Methods: The GENIUS Program is a school-based intervention consisting of nutrition education (thematic materials and healthy snack-related materials) and the provision of nutritious snacks (20 sessions) for elementary school children. The program was initiated by the National Food Agency (Badan Pangan Nasional [BAPANAS]) and its implementation, monitoring, and evaluation were coordinated by the Indonesian Association of Higher Education Institutions in Nutrition (Asosiasi Institusi Pendidikan Tinggi Gizi Indonesia [AIPGI]) in collaboration with local universities in the program areas. This quantitative study used a secondary data design based on the implementation of the GENIUS Program conducted from October to November 2023 in three public elementary schools in Binjai City, North Sumatra. The researchers were also involved in data collection. A total of 205 students in grades 4–6 were included in the study. Pre- and Post-test knowledge data were collected using a questionnaire. Data were analyzed using a paired t-test (for normally distributed data) or the Wilcoxon signed-rank test (for non-normally distributed data), as well as the Kruskal–Wallis test. Results: The findings showed a significant increase in nutrition knowledge scores before and after the intervention (p-value<0.05). In addition, there were significant differences in knowledge improvement among schools (p-value=0.008). Further post-hoc analysis indicated that some schools achieved greater improvements in knowledge scores than others. Conclusions: The GENIUS Program was effective in improving nutrition knowledge among elementary school students, although the magnitude of improvement varied across schools.